Artificial Intelligence in External Public Audit and its Role in the Management of Risk Areas in the Public Sector - Teodora Nicoleta Lazar (Plesa); Constanta Popescu (Risk in Contemporary Economy)
The use of artificial intelligence is the newest trend in society, and the benefits of its use are more than obvious. Currently, the massive digitization process, which has intensified during the COVID 19 pandemic, has favored the development of artificial intelligence. At the level of the public sector, in some states the digitization phenomenon has almost reached its end, this being possible due to their degree of development. This developed the use of artificial intelligence as the next step in their evolution. The supreme audit institutions are no exception to this rule. Some of these have managed, through internal structures, to develop real tools based on artificial intelligence to support external public auditors in carrying out their audit missions. The paper aims to analyze the main challenges related to the use of artificial intelligence in external public audit and the ways to respond to these challenges.